Aktivitas Layanan Digital Lembaga Polri dalam Memberi Informasi kepada Masyarakat (Studi Kasus di Kota Depok) - Nainggolan, Maringan; Anom, Erman (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study examines the effectiveness of the Indonesian National Police’s (Polri) digital services in Depok City, focusing on information dissemination, implementation challenges, and public perceptions. Using a qualitative case study approach with interviews, observations, and documentation, the findings reveal that Polri's digital services have improved communication, accelerated information delivery, and simplified administrative access. However, challenges remain, including limited infrastructure, low digital literacy among some groups, insufficient personnel skills, and poor system integration. While public perception is generally positive especially among younger users elderly and marginalized communities still face access barriers. The study concludes that although Polri’s digital transformation shows promise, further improvements in infrastructure, human resources, and inclusive outreach are needed to ensure equitable and effective public service.